Flow responses alteration by geometrical effects of tubercles on plates under the maximal angle of attack. (October 2021) - Mu, KS; Kueh, ABH; Shek, PN; Mohd Haniffah, MR; Tan, BC
Plates with leading-edge tubercles experience beneficially more gradual aerodynamics stalling when entering the post-stall regime. Little is known, however, about the corresponding aquatic flow responses when these tubercles-furnished plates are subjected to the maximal angle of attack, with the flow direction perpendicular to their planar area. Hence, this study presents numerically, by means of the flow behavior solver ANSYS, the flow responses alteration in terms of the geometrical effects of tubercles on plates through changes in amplitudes (5 mm, 10 mm, 15 mm) and wavelengths (50 mm, 100 mm, 150 mm) under the maximal angle of attack in comparison to a control case, i.e., without tubercles. Additional to the commonly examined flow velocity and pressure, characteristics such as wake (area, reattachment length, flow recirculation intensity) and newly defined downstream vortical parameters (area, perimeter, and Feret diameters) for the vortex region have been proposed and assessed. It is found that the drag increases with the tubercle wavelength but corresponds inversely with the tubercle amplitude. By correlating with the best beneficial velocity and pressure profiles, it has been characterized that the optimally performing plate is the one that generates the greatest flow recirculation intensity, wake area, and reattachment length, corresponding to the capability to produce also the highest vortical area, perimeter, and major Feret diameter. Compared to the control case, all plates with tubercles alter beneficially these flow behaviors. In conclusion, plates with tubercles contribute favorably to the flow behaviors under the maximal angle of attack compared to the control case while the newly proposed downstream parameters could serve capably as alternatives in corroborating the flow physics description in future studies.